[en] DIALOGUES WITH THE SPHINX: CLARICE IN THE ENGLISH LANGUAGE - MARCELA LANIUS (MAXWELL, 2017)
[pt] A presente dissertação busca analisar o modo como Clarice Lispector foi traduzida e lida em língua inglesa. Desse modo, serão pontuados os contextos históricos e os agentes de dois projetos distintos de tradução: o primeiro, ocorrido entre as décadas de 1960 e 1990, que situou Clarice como uma escritora sobretudo acadêmica e feminista; e o segundo, que vem ocorrendo desde o ano de 2009 e que teve como ponto inicial a biografia de Clarice escrita por Benjamin Moser, no qual Clarice figura como uma escritora estrangeira e canônica. As vertentes teóricas que embasam este trabalho, provenientes dos Estudos da Tradução e que sofreram o impacto da chamada virada cultural da área, auxiliarão na análise dos paratextos que cercam as traduções aqui discutidas, uma vez que atribuem um papel ativo ao tradutor e enxergam a tradução como instrumento de consagração de um autor. Desse modo, a teoria da invisibilidade do tradutor, proposta por Lawrence Venuti, os conceitos de patronagem e reescrita, de Lefevere, e os estudos desenvolvidos por Luise von Flotow e Sherry Simon, que vinculam a tradução às questões de gênero, serão peças integrais para que possamos analisar as diferentes imagens de Clarice Lispector criadas pela via da tradução. === [en] The main purpose of this thesis is to analyze the translation into English of Brazilian writer Clarice Lispector s books and the different readings of her work which surfaced in that language. With that in mind, the historical contexts as well as the agents behind two distinct translation projects will be analyzed: the first project, which took place between the decades of 1960 and 1990, and understood Clarice as an academic and feminist writer; and the second project, which began in 2009 with Lispector s biography, written by Benjamin Moser, and placed her as a foreign and canonical writer. The theoretical frameworks employed in this thesis all originate in the field of Translation Studies and were influenced by the so-called cultural turn. They will be applied to analyze the paratexts accompanying the various translations discussed herein, since they afford the translator a more active role and view the act of translation as a way of acknowledging an author. Thus, the notion of translator s invisibility proposed by Lawrence Venuti, the concepts of patronage and rewriting of Andre Lefevere, and the studies developed by Luise von Flotow and Sherry Simon, linking translation and gender, are essential for analyzing the different images of Clarice Lispector created through translation.